The love levanter podcast / Fatimah Maksuumah Mohamad Zain and Haniza Sarijari - Mohamad Zain, Fatimah Maksuumah; Sarijari, Haniza (Academy of Language Studies, 2023)
As the awareness of mental health increases, people all across the internet are talking more about attachment styles and how it influences and manifests in adult relationships. Attachment is the strong emotional connection a kid develops with their caregiver. The nature of this bond is crucial for children's emotional and social growth (Cristobal, Santelices, & Fuenzalida, 2017). It also has a long-lasting impact on the character of upcoming relationships and wellbeing. The lack of these qualities with parents, may cause a deep-rooted childhood trauma that later manifests as insecure attachment style. There are three different types of insecure attachment styles which are avoidant, anxious, and fearful-avoidant. The main purpose of creating this podcast is to bring self-awareness to people about their attachment style and childhood trauma and how to work through it. A survey was carried out using a Google Form and it was discovered that The Love Levanter Podcast provides a mechanism for people to effectively and amusingly study the consequences of childhood trauma on adult attachment styles. The Love Levanter Podcast is the ideal way to inspire listeners to learn about their behaviours while also generating an exciting moment, which would help the audience realise if they could discover all the information, they require in one convenient location.